Peran Pesantren dalam Penguatan Moderasi Beragama di Indonesia - Khoirul Fatih, Moh (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
Religious pluralism and diversity are undeniable social facts. Indonesia is a country composed of various ethnicities, religions, and races. Furthermore, social conflicts in the name of religion have persisted to this day. This issue arises because many religious followers in Indonesia tend to prioritize exclusive and radical ideologies, resulting in rigid and harsh characters. Educational institutions, particularly Islamic boarding schools (pesantren), play a crucial role in mitigating these religious conflicts in Indonesia. One of their significant roles is instilling strong religious moderation, thereby producing pesantren alumni who can become peace agents for Indonesia and the world. Given its function as an Islamic educational institution, pesantren is a vital place for spreading both inclusive and exclusive religious values. However, pesantren are expected to function as Islamic educational institutions that can produce moderate and tolerant students. This goal can be achieved through religious education focused on the values of religious moderation.